Utilization of galiang (Cyrtosperma merkusii) flour in the production of chocolate chip cookies - Sevilla, Maria Theresa Pili (University of the Philippines Diliman, 1999)
The study was conducted to formulate galiang-based chocolate chip cookies, with the highest level of substitution of all-purpose flour with galiang flour without significantly (α = 0.05) affecting the sensory properties of the product. A preliminary study was done to establish a narrowed down range (96%, 97%, 98%, and 99%) and to choose and modify the recipe. Phase I (Formulation of chocolate chip cookie with the maximum level of substitution of all-purpose flour with galiang flour) showed that the chocolate chip cookies having 95% galiang flour were most acceptable compared with the samples having other substitution levels, making it the base formulation. This was done based on the evaluation of their general acceptability and sensory characteristics. In Phase II (Assessment of the replicability of the chocolate chip cookies with the selected level of substitution of all-purpose flour with galiang flour), sensory evaluation results treated with ANOVA showed no significant difference (α = 0.05) among the samples, proving the replicability of the formulation. Phase III (Analyses of the chemical, microbiological properties, and cost of the control and experimental chocolate chip cookies) showed that the chocolate chip cookies with galiang flour had higher levels of moisture, crude fat, crude fiber, total available carbohydrates and ash and lower values for crude protein content compared with the base formulation. For the microbiological properties, the control and experimental choclate chip cookies were relatively the same in coliform, yeast and mold count. However, in terms of the total anaerobic count, the chocolate chip cookies with galiang flour showed a much higher count (<250 cfu/g) than the control (<100 cfu/g). The cost of the experimental chocolate chip cookies was higher than that of the control by P0.18.